Media Influence on Revictimization of Sexual Crime Victims: A Qualitative Study of Revenge Porn Cases in Indonesia - Dahlan, Rudiyanto; Fathussalam, Muhammad Fikri (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
This research discusses the phenomenon of revictimization of women in the context of technology-based sexual violence, specifically revenge porn and blackmail. Women victims are forced to remain in a sexual relationship with the perpetrator-who is generally a partner or ex-partner-with the threat of spreading intimate footage to social media. This phenomenon causes serious psychological impacts, including depression, rejection from the social environment, failure to report to law enforcement, and victim blaming. This research aims to provide an in-depth understanding of the forms of revictimization experienced by women and the protection solutions that can be provided through the legal system and social approaches. The research method used is descriptive qualitative with data collection techniques through in-depth interviews with three informants who are victims of revenge porn. The results showed that the media played a significant role in exacerbating victims' suffering through the dissemination of sexually exploitative material. This research also provides recommendations for human rights-based protection policies and strategies as well as the urgency of public education in combating digital sexual violence.